The Influence of Perceived Organizational Support on Work Meaningfulness and Its Impact on Employee Life Satisfaction and Employee Creativity - Jujun Juhedi; widodo; Zaenal Mustafa El Qadri; Wisnu Prajogo (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the influence of Perceived Organizational Support (POS) on Work Meaningfulness and its impact on Employee Life Satisfaction and Employee Creativity among Civil Servants in the Public Order Police Unit (Satpol PP) in West Java. The study population includes 338 civil servants from the Satpol PP in five regions (Cirebon Regency, Kuningan Regency, Majalengka Regency, Cirebon City, and Indramayu Regency). The research sample was determined using the 10:1 rule of thumb approach (Hair et al., 2019), based on the number of indicators, which is 17, resulting in a minimum requirement of 170 respondents. Sample distribution was done proportionally in each region, while respondent selection in the second stage used convenience sampling as a form of multi-stage sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with the assistance of AMOS. The research findings indicate that (1) POS has a positive effect on employee life satisfaction and employee creativity; (2) POS has a positive effect on work meaningfulness; (3) work meaningfulness has a positive effect on employee life satisfaction and employee creativity; and (4) work meaningfulness is proven to mediate the relationship between POS and both employee life satisfaction and employee creativity. These findings confirm that organizational support not only directly enhances employees' life satisfaction and creativity but also indirectly increases work meaning. Therefore, human resource management strategies at Satpol PP need to focus on improving the perception of organizational support and creating work meaning to strengthen the well-being and creativity of civil servants in the local government work environment.